Thermal performance of a silica gel-water vapor adsorption system as an alternative cooling technology - Katana, Katarzyna; Szelągowski, Adam; Grzebielec, Andrzej (International Conference “Environmental Engineering”, 2026)
Adsorption-based cooling is an alternative to conventional vapor-compression systems that have a high environmental impact and account for a significant share of global energy consumption. This study presents an experimental and analytical investigation of a two-bed adsorption cooling system operating with a water/silica-gel working pair. The device consists of a refrigerant circuit (water vapor) and a secondary water circuit that provides supplies or removes heat from the beds when necessary. The refrigerant circuit includes two adsorption beds, a condenser, an expansion valve, and an evaporator. The system operates in alternating half-cycles, with one bed undergoing desorption while the other performs adsorption. Measurements of temperature, pressure, and volumetric flow rates were conducted over nearly three half-cycles. Theoretical cooling capacity was calculated at 6.652 kJ, which corresponds to the EER (Energy Efficiency Ratio) equal to 0.0405. To overcome issues associated with limited thermal contact between the surface of the heat exchanger and the adsorbent particles as well as low thermal conductivity of silica gel, it should be applied directly onto the heat exchanger’s surface in the form of coatings instead of the traditional loose packing of adsorbent granules. Additionally, enhancing the system’s performance can be achieved by implementing heat and mass recovery. These findings provide insights into the design of adsorption-based refrigeration, emphasizing environmentally friendly and efficient alternatives to conventional vapor-compression systems.
Keywords: adsorption; silica gel; cooling; refrigeration; energy efficiency